Acceleration demands in single-storey RC buildings with flexible diaphragms. (15th January 2023) - Ruggieri, Sergio; Vukobratović, Vladimir
Highlights: Investigation of the diaphragm flexibility influence on PFAs and FRS. Parametric analysis on a large sample of idealized single-storey RC buildings. Simultaneous influence of diaphragm flexibility and structural nonlinearities. Formulations of PFA and FRS ratios in buildings with rigid and flexible diaphragms. Assessment of the proposed formulations on an existing case study building. Abstract: This paper presents a study on acceleration demands in single-storey reinforced concrete (RC) buildings with flexible diaphragms, expressed through peak floor accelerations (PFAs) and floor response (acceleration) spectra (FRS). Firstly, an extensive parametric study was performed on idealized single-storey buildings for which geometrical parameters were varied for inducing different degrees of diaphragm flexibility. The influence of diaphragm flexibility was taken into account through the commonly used in-plane displacement ratio. To investigate acceleration demands, three sets of Eurocode 8 spectrum-compatible ground motion records were used as input, selected according to three different soil categories. RC buildings were considered as both linear elastic and nonlinear, whereas non-structural components (NSCs) were considered only as linear elastic. In all cases, it was observed that diaphragm flexibility significantly influences PFAs and FRS, which can both increase and decrease compared to buildings with rigid diaphragms. In the case of FRS, a shifting of peaks was observed as well. Despite the very complicated dependence between the diaphragm flexibility and PFAs and FRS, based on the obtained results, simple empirical formulas for the estimation of the ratios between PFAs and FRS in RC buildings with rigid and flexible diaphragms were proposed. Their accuracy was assessed through a case study example performed on an existing single-storey RC building.